Intrinsic Motivation, Competence and Affective Commitment have on Performance - Nurhandayani, Syifa (Almana : Jurnal Manajemen dan Bisnis, 2025)
PT. Parkland World Indonesia is one of the companies that produces shoes and is competing to become a pioneer in the shoe market that can meet market needs amidst the need for improvements in terms of human resource performance in order to produce shoes with good results and in accordance with the standards set. This study aims to determine how much influence Intrinsic Motivation, Competence, and Affective Commitment have on Performance in the Development of PT. Parkland World Indonesia. The data sources in this study use primary and secondary sources and have 139 respondents from the Development of PT. Parkland World Indonesia. Data analysis is quantitative in nature with the aim of testing the established hypothesis and using multiple linear regression analysis calculations. In processing and analyzing data, the SPSS 25 application is used. From this study, it was concluded that Intrinsic Motivation, Competence, and Affective Commitment have a significant influence on the Development Performance of PT. Parkland World Indonesia. Judging from the calculations using multiple linear regression analysis, the results show that the Competence variable has the greatest influence on Performance, then the one with the greatest influence is Intrinsic Motivation, and the one with the smallest influence of the three independent variables is Affective Commitment to Performance.